Long-term outcomes of 307 patients after complete thymoma resection - Zu-Yang Yuan; Shu-Geng Gao; Ju-Wei Mu; Qi Xue; You-Sheng Mao; Da-Li Wang; Jun Zhao; Yu-Shun Gao; Jin-Feng Huang; Jie He (Chinese Journal of Cancer, 2017)
Abstract Background Thymoma is an uncommon tumor without a widely accepted standard care to date. We aimed to investigate the clinicopathologic variables of patients with thymoma and identify possible predictors of survival and recurrence after initial resection. Methods We retrospectively selected 307 patients with thymoma who underwent complete resection at the Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College (Beijing, China) between January 2003 and December 2014. The associations of patients’ clinical characteristics with prognosis were estimated using Cox regression and Kaplan–Meier survival analyses. Results During follow-up (median, 86 months; range, 24–160 months), the 5- and 10-year disease-free survival (DFS) rates were 84.0% and 73.0%, respectively, and the 5- and 10-year overall survival (OS) rates were 91.0% and 74.0%, respectively. Masaoka stage (P < 0.001), World Health Organization (WHO) histological classification (P < 0.001), and postoperative radiotherapy after initial resection (P = 0.006) were associated with recurrence (52/307, 16.9%). Multivariate analysis revealed that, after initial resection, WHO histological classification and Masaoka stage were independent predictors of DFS and OS. The pleura (25/52, 48.0%) were the most common site of recurrence, and locoregional recurrence (41/52, 79.0%) was the most common recurrence pattern. The recurrence pattern was an independent predictor of post-recurrence survival. Patients with recurrent thymoma who underwent repeated resection had increased post-recurrence survival rates compared with those who underwent therapies other than surgery (P = 0.017). Conclusions Masaoka stage and WHO histological classification were independent prognostic factors of thymoma after initial complete resection. The recurrence pattern was an independent predictor of post-recurrence survival. Locoregional recurrence and repeated resection of the recurrent tumor were associated with favorable prognosis.